2002
DOI: 10.1074/jbc.m206479200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Electron Paramagnetic Resonance Approach to Determine the Mechanism of Drug Transport by P-glycoprotein

Abstract: ATP-driven pumping of a variety of drugs out of cells by the human P-glycoprotein poses a serious problem to medical therapy. High level heterologous expression of human P-glycoprotein, in the yeast Saccharomyces cerevisiae, has facilitated biophysical studies in purified proteoliposome preparations. Membrane permeability of transported drugs and consequent lack of an experimentally defined drug position have made resolution of the transport mechanism difficult by classical techniques. To overcome these obstac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
78
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 24 publications
(24 reference statements)
6
78
0
Order By: Relevance
“…The histidine-tagged mutants were expressed in HEK 293 cells, isolated by nickel-chelate chromatography, and assayed for verapamil-stimulated ATPase activity. Verapamil was used because it is transported by P-gp (35) and it highly stimulates the ATPase activity of human P-gp (over 10-fold) (36). It was found that the activity of all three mutants was similar to that of wild-type P-gp (Fig.…”
Section: Mutations In Ih2 But Not Ih1 Inhibit Maturation Of P-gp-mentioning
confidence: 96%
See 2 more Smart Citations
“…The histidine-tagged mutants were expressed in HEK 293 cells, isolated by nickel-chelate chromatography, and assayed for verapamil-stimulated ATPase activity. Verapamil was used because it is transported by P-gp (35) and it highly stimulates the ATPase activity of human P-gp (over 10-fold) (36). It was found that the activity of all three mutants was similar to that of wild-type P-gp (Fig.…”
Section: Mutations In Ih2 But Not Ih1 Inhibit Maturation Of P-gp-mentioning
confidence: 96%
“…P-gp can be trapped at a transition state during ATP hydrolysis by including vanadate in the reaction mix (35). Vanadate traps ADP at either NBD by mimicking the transition state of the ␥-phosphate of ATP during hydrolysis, and trapping at one NBD inhibits ATP hydrolysis at the second site (35). Vanadate trapping of nucleotide causes conformational changes in P-gp, and this can be detected by disulfide cross-linking analysis (36).…”
Section: Mutations In Ih2 But Not Ih1 Inhibit Maturation Of P-gp-mentioning
confidence: 99%
See 1 more Smart Citation
“…Spin labeled drugs have been synthesized and used to study the drug mechanisms at a molecular level for a long time. [11][12][13] Besides their reporter properties, nitroxides are also used in anti-oxidant therapies for several diseases because they can effectively scavenge the reactive oxygen species and therefore improve cell viability. 14,15 Here, we use continuous wave (cw) EPR spectroscopy as an alternative technique to study the interaction between drugs and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…One major advantage of cw EPR spectroscopy is the ability to observe the unbound drug and the bound drug simultaneously, due to its sensitivity to the rotational dynamics of the radicals. [11][12][13] Bound spin labeled molecules (immobilized) have characteristic broad signals stemming from restricted rotational motion, and unbound spin labeled molecules (mobilized) have sharp three-line signals coming from freely tumbling motion. [16][17][18] Salicylic acid (SA), which is a non-steroidal anti-inflammatory drug, and serum albumin, which is the most abundant plasma protein, were used as a model drug and transporter protein, respectively.…”
Section: Introductionmentioning
confidence: 99%